CEO-TMT overseas experience differences and firm performance: A self-categorization theory perspective - Zhaocheng Xu (Heliyon, 2023)
Based on upper echelons and self-categorization theories, this study empirically examines the relationship between CEO-top management team (TMT) overseas experience differences and firm performance and the moderating effects of hometown connectedness, ownership nature, and environmental dynamics. We use data on Chinese manufacturing listed companies from 2012 to 2021. The results show that CEO-TMT overseas experience differences significantly and negatively affect firm performance. Hometown connectedness positively moderates this relationship; as CEO-TMT hometown connectedness increases, the negative impact of CEO-TMT overseas experience differences on firm performance decreases. Finally, state ownership and higher environmental dynamics mitigate the negative relationship between CEO-TMT's overseas experiences and firm performance.